Exploration of food-seeking behaviour, food preparation, and restrictions to sufficient food among the Jahai sub-tribe (indigenous people) in Gerik, Malaysia - Gan, Wan Ying; Sulaiman, Norhasmah; Law, Leh Shii; Zalbahar @ Zabaha, Nurzalinda; Ahmad Fuzi, Salma Faeza; Wilkes, Martin A. (MDPI, 2020)
Access to food has been determined to be a factor that strongly influences the dietary intake and eating habit of indigenous people (Orang Asli, OA). This study explored food acquisition and the barriers in obtaining traditional and market foods among the Jahai subtribe (within the Negrito ethnic group) via a qualitative approach. Twenty-eight OA (14 males and 14 females) from Gerik, Perak, Malaysia participated in four focus group discussions (FGDs; two male-only and two female-only groups; seven informants in each FGD). Thematic analysis was adopted to analyse the gathered data. The results found that the Jahai applied both modern (buying and receiving food assistance) and traditional (gathering, farming, fishing, and hunting) methods in obtaining food. The barriers they faced in gathering sufficient food supply included low purchasing power, high demand for food, high transport costs, depletion of food supplies in their surroundings, threats from wild animals on the farm and during food searching activities, and food sharing. Food preparation methods practiced by the OA include roasting and grilling, frying, simmering (gulai), and boiling. In conclusion, this study enhances our understanding of the dietary behaviour of the Jahai subtribe and highlights restricted food access among the OA, which demands urgent attention.